Chelystachya, a new genus of the subtribe Polystachyinae (Orchidaceae) - Mytnik-Ejsmont, Joanna; Szlachetko, Dariusz; Górniak, Marcin (Biodiversity: Research and Conservation, 2012)
A new genus of Orchidaceae (Polystachyinae), Chelystachya Mytnik & Szlach. is described and illustrated basing on results of molecular and morphological studies. It is related to Polystachya Hook. but is distinct in having large, single-noded, spherical, succulent pseudobulbs flattened on the substratum, pendent and densely pubescent inflorescence, lowermost lip, and lip veins directed to the lip base. Results of phylogenetic analyses based on plastid markers validate the reason for a new genus. Keys for determination of all genera of the subtribe Polystachyinae and both species of Chelystachya are included. Two new combinations are made. A comprehensive description and full synonymy, as well as detailed ecological, phenological and distribution data and a list of 125 examined specimens are provided for each taxon treated. Because Polystachya affinis Lindl. is considered a holotype of Polystachya Hook. sect. Affines Kraenzl., this name is automatically a synonym of the newly introduced generic name Chelystachya. Other species of the former section Affines are classified within the section Humiles.